Long-term Care Facility Variation in the Incidence of Pneumonia and Influenza - Bosco, Elliott (Open Forum Infect Dis, 2019)
BACKGROUND: Pneumonia and influenza (P&I) increase morbidity and mortality among older adults, especially those residing in long-term care facilities (LTCFs). Facility-level characteristics may affect the risk of P&I beyond resident-level risk factors. However, the relationship between facility characteristics and P&I is poorly understood. To address this, we identified potentially modifiable facility-level characteristics that influence the incidence of P&I across LTCFs. METHODS: We conducted a retrospective cohort study using 2013–2015 Medicare claims linked to Minimum Data Set and LTCF-level data. Short-stay (<100 days) and long-stay (100+ days) LTCF residents were followed for the first occurrence of hospitalization, LTCF discharge, Medicare disenrollment, or death. We calculated LTCF risk-standardized incidence rates (RSIRs) per 100 person-years for P&I hospitalizations by adjusting for over 30 resident-level demographic and clinical covariates using hierarchical logistic regression. RESULTS: We included 1 767 241 short-stay (13 683 LTCFs) and 922 863 long-stay residents (14 495 LTCFs). LTCFs with lower RSIRs had more licensed independent practitioners (nurse practitioners or physician assistants) among short-stay (44.9% vs 41.6%, P < .001) and long-stay residents (47.4% vs 37.9%, P < .001), higher registered nurse hours/resident/day among short-stay and long-stay residents (mean [SD], 0.5 [0.7] vs 0.4 [0.4], P < .001), and fewer residents for whom antipsychotics were prescribed among short-stay (21.4% [11.6%] vs 23.6% [13.2%], P < .001) and long-stay residents (22.2% [14.3%] vs 25.5% [15.0%], P < .001). CONCLUSIONS: LTCF characteristics may play an important role in preventing P&I hospitalizations. Hiring more registered nurses and licensed independent practitioners, increasing staffing hours, and higher-quality care practices may be modifiable means of reducing P&I in LTCFs.